Analisis Profil ADMET Senyawa Tanaman Ceremai (Phyllanthus acidus) secara In-Silico - Hamdan Ramdani; Taufik Muhammad Fakih; Aden Dhana Rizkita (Bandung Conference Series: Pharmacy, 2026)
Abstract. Ceremai or Phyllanthus acidus is a plant that is widely distributed in various regions of Indonesia. In several studies, compounds found in ceremai have been shown to have pharmacological activity. Before a compound can be used as a medicine, pharmacokinetic and toxicity studies are also required to ensure that the compound is acceptable to the body. Research using an in-silico approach can be conducted to analyze the pharmacokinetic profile and toxicity of compounds found in ceremai. The results of pharmacokinetic predictions for the compounds Hirsutrin; Quercetin 3-O-alpha-L-rhamnoside; Quercetin 3-rutinoside; Myricitrin; Phyllanthusol A; and Phyllanthusol B show poor absorption in the gastrointestinal tract, do not cross the blood-brain barrier, do not inhibit cytochrome P450 enzymes, and do not meet Lipinski's rules. All six compounds also have the potential to cause nephrotoxicity and respiratory toxicity if administered at doses exceeding the predicted LD50. Abstrak. Ceremai atau Phyllanthus acidus merupakan tanaman yang tersebar diberbagai daerah di Indonesia. Dalam beberapa penelitian senyawa yang terdapat di dalam ceremai mempunyai aktivitas farmakologi. Sebelum suatu senyawa dapat dijadikan obat diperlukan juga studi farmakokinetika dan juga toksisitas untuk memastikan senyawa tersebut dapat diterima oleh tubuh. Penelitian menggunakan pendekatan in-silico dapat dilakukan dalam menganalisis profil farmakokinetika dan juga toksisitas dari senyawa yang terdapat di dalam ceremai. Hasil prediksi farmakokinetika dari senyawa Hirsutrin; Quercetin 3-O-alpha-L-rhamnoside; Quercetin 3-rutinoside; Myricitrin; Phyllanthusol A; dan Phyllanthusol B menunjukkan penyerapan dalam saluran cerna yang kurang baik, tidak menembus BBB, dan tidaka ada enzim sitokrom P450 yang dihambat, dan juga keenam senyawa tidak memenuhi aturan lipinski. Keenam senyawa juga berpotensi menyebabkan nefrotoksik dan respiratotoksik jika diberikan melebihi prediksi dosis LD50.